Relationships between fear of cancer recurrence, anxiety and worry, and health behaviors and health service use: a systematic review. Issue 4 (8th October 2021) - Reed, Sarah C.; Berrett-Abebe, Julie; Whitney, Robin L.; Sarkar, Sayantani; Bell, Janice F.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: This systematic review was conducted to improve our understanding of the relationship between fear of cancer recurrence (FCR), anxiety and worry, and engagement in health behaviors and/or health service use. Methods: A systematic review following PRISMA methodology was performed to identify any publications that examined FCR, anxiety and worry, and health behaviors and/or health service use in the following databases: PubMed, CINAHL, and PsychINFO from January 1990 to April 2021. Quality was assessed using QualSyst, a standard quality assessment for evaluating primary research articles. Results: Seventy articles met the inclusion criteria, but the outcomes were too heterogeneous to combine in statistical meta-analysis. The measurement of FCR also varied widely and was inconsistent across studies. Among FCR specific measures, 36% used some version of the Fear of Cancer Recurrence Inventory. Prevention and detection of new and recurrent cancers accounted for 60% of all included studies, with the most frequently examined health behaviors being smoking status (17%) and physical activity (16%). Most associations indicated a significant relationship between FCR and current smoking, with those who are currently smoking experiencing higher levels of FCR. Relatively few studies explored the relationship between FCR and surveillance. Associations categorized under Interventions for Late Effects included a range of health services use with largely mixed results. Overall, studies had moderate to high quality. Conclusions: Given the measurement heterogeneity of FCR, future research would benefit from consistent operationalization and measurement. Some evidence suggests that FCR is associated with poor health behaviors. More studies are needed examining the relationship between FCR and surveillance. Research and clinical interventions may choose to focus on early post-treatment survivorship, given greater opportunities for support and intervention around FCR and other psychosocial concerns.